Portia Zvavahera - Brown, Meredith (David Zwirner Books, 2023)
Expressive and rich paintings by the Zimbabwean artist Portia Zvavahera—made during a time of intense solitude and collective struggle across the globe. In her paintings, Zvavahera gives form to emotions that manifest from other realms and dimensions beyond the domains of everyday life and thought. Her vivid imagery is rooted in the cornerstones of our earthly existence—life and death, pain and pleasure, isolation and connection, and love and loss. Zvavahera draws from a powerful visual vocabulary comprising women, her family, and shape-shifting animals, in scenes both metaphorical and fantastical. In several paintings, she makes use of intricate patterns taken from her own floral or classical Zimbabwean designs. Her particular process of alternating painting and printing results in images that communicate complex emotions in a play of tension and release. The result is a deeply personal body of work that probes the nature of the human condition. As Zvavahera states, "It is me in the paintings.… I can only speak about myself." In addition to gorgeous reproductions of twenty-four paintings, including up-close details and installation views, this catalogue also features a new essay by the curator Meredith Brown and an interview with the artist by the writer Allie Biswas. This catalogue surveys work made since 2017
Keywords: Zvavahera, Portia -- 1985-; afriška umetnost; slikarstvo 21.st; abstraktna figuralika; motiv živali; motiv ptice; Bildband